Sintese de naftoquinonas acopladas à fluoróforos bodipys: atividade antitumoral e estudos de localização subcelular - Talita Bárbara Gontijo (2017)
The majority of chemotherapeutic agents in use for the management of cancer are not selective, causing several adverse effects to patients. For this reason, there is a lot of research being conducted currently aiming at the development of new and more selective substances. Studies of mechanism of action of bioactive substances can contribute to the rational molecular design of more selective derivatives, and one of the methods more frequently used to achieve this goal are subcellular localization studies. The naphthoquinones constitute a promising class of chemotherapeutic agents, but subcellular localization studies for these substances are not so feasible because the production of luminescent naphtoquinoidal derivatives is a major challenge nowadays. In this work, we describe the synthesis and total characterization of six new naphthoquinones- based BODIPY. The synthesis was accomplished via a convergent synthetic route, using a classical click chemistry reaction to join the quinone and BODIPY moieties In vitro tests using different tumor cell lines were performed with compounds 56-60, and the results indicated that two of these compounds were active. The photophysical properties of fluorescent derivatives (60) and (61) were studied by means of absorption and emission spectra, To the best of our knowledge, the present study reports for the first time the synthesis of fluorescent lapachone-based BODIPY. Subcellular localisation studies with tumor cell lines were performed for the compound (60), showing that this probe was a specific mitochondria-staining agent.